Socialization of the prevention and Eradirection of Dengeu Fever (DHF) and Covid-19 in Pematang Kuala Vilage, Sub District Teluk Mengkudu, Serdang Bedagai Regency in 2021 - Ritonga, Fajar Utama; Thamrin, Husni; Suriadi, Agus (Talenta Publisher, 2022)
Socialization is an activity to provide information from individuals to individuals and individuals to groups where this socialization has goals and benefit to the recipient of the information. The purpose of the work program for Kuliah Kerja Nyata (KKN)) this is to provide knowledge and understanding to the community in Pematang Village Kuala about the diseases caused by this virus, namely Covid-19 and Dengue Fever Dengue (DHF). The method used in carrying out this activity is lectures and lectures question and answer and share information. This socialization is carried out in order to add insight the community and provide understanding to the Pematang Kuala Village. The result of this service is that the Pematang Kuala Village community knows the differences and symptoms of the Covid-19 disease with Dengue Fever (DHF) and becomes brave to seek treatment at health services.